STRATEGIC DIRECTION OF DEVELOPMENT «HOUSING AND COMMUNAL SERVICES AND URBAN ENVIRONMENT» IN STAVROPOL TERRITORY - A. Kazarova (Вестник университета, 2018)
In work results of the federal projects directed to improvement of quality of life of citizens by means of improvement of settlements are considered and analyzed; the possible actions promoting formation of the comfortable urban environment are presented. The goals and objectives of the priority project «Urban environment», as well as the directions of improvement programs are studied. The analysis of the results of the implementation of the priority project «Formation of a comfortable urban environment» has been made, the results of which presented a rating of regions in which the Stavropol territory in the leaders at the end of 2017.